Lives of the explorers : discoveries, disasters (and what the neighbors thought) - Krull, Kathleen (HMH Books for Young Readers, 2014)
"You might know that Columbus discovered America, Lewis and Clark headed west with Sacajawea, and Sally Ride blasted into space. But what do you really know about these bold explorers? What were they like as kids? What pets or bad habits did they have? And what drove their passion to explore unknown parts of the world? With juicy tidbits about everything from favorite foods to first loves, Lives of the Explorers reveals these fascinating adventurers as both world-changers and real people. The entertaining style and solid research of the Lives of. series of biographies have made it a favorite with families and educators for twenty years. This new volume takes readers through the centuries and across the globe, profiling the men and women whose curiosity and courage have led them to discover our world"--